Bimbingan Karir Dalam Mengembangkan Enterpreneurship Remaja Putus Sekolah Di Uptd Pelayanan Sosial Bina Remaja Raden Intan Lampung: Career Guidance in Developing Entrepreneurship of School Dropouts at the Raden Intan Lampung Youth Development Social Services Unit - Noffiyanti tanjung; Berlian Rahmawati; Julia Shasmita (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2022)
There are still many school dropouts who are still confused about developing entrepreneurship and are not yet ready for the future. It is hoped that with this guidance, teenagers will be able to develop entrepreneurship through skills programs so that these teenagers can become independent individuals because they already have skills and develop their potential. Thus, providing career guidance to school dropouts is very much needed as a form of support to help them find direction and be motivated. This type of research is field research, the approach used by the author is a qualitative approach with a descriptive nature. The data collection techniques used are observation, interviews, and documentation. Of the 19 teenagers and using the Purposive Sampling Technique. So the primary data sources in the study were 6 school dropouts, 1 social worker, and 1 skills instructor. The data analysis technique in this study uses several steps, namely, data reduction, data presentation, and verification or drawing conclusions. The results of career guidance show that First, the formation stage is the activity carried out by inserting oneself into the activity. Second, the transition stage is the group leader or social worker explaining the purpose of the activity, observing whether the members are ready to undergo the next stage. Third, the activity stage in this guidance activity stage, the method used is discussion and also Q&A conducted by social workers to adolescents. Fourth, the ending stage of the activity carried out, namely asking group members again about their understanding of the material that has been given, then they are asked to convey their impressions and messages during the process. Keywords: Career Guidance, School Dropouts, Entrepreneur